2015
DOI: 10.1111/jfpp.12592
|View full text |Cite
|
Sign up to set email alerts
|

Combined Application of Carboxymethyl Chitosan Coating and Brassinolide Maintains the Postharvest Quality and Shelf Life of Green Asparagus

Abstract: The combined effects of carboxymethyl chitosan (CMCH) coating and brassinolide (BR) on the sensory quality and physicochemical characteristics of green asparagus (Asparagus officinalis L.) stored at 4 ± 1C and 90-95% relative humidity for 24 days were investigated. The combined treatment (CMCH + BR) inhibited respiration rate and water loss, maintained higher concentrations of ascorbic acid, total phenolics and DPPH (2,2-diphenyl-1-picrylhydrazyl) radical-scavenging activity, and restrained the increase of mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…Our findings are supported by Zhou et al [2008] where by using brassinolide, Huanghua pears water loss was decreased. Also, Wu and Yang [2016] showed that the asparagus spears treated with brassinolide had a significantly lower weight loss during storage. Epibrassinolide declined fruit weight loss by retarding the respiration rate and physiological metabolisms during postharvest life of peach and jujube fruit [Zhu et al 2010, Ge et al 2016.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our findings are supported by Zhou et al [2008] where by using brassinolide, Huanghua pears water loss was decreased. Also, Wu and Yang [2016] showed that the asparagus spears treated with brassinolide had a significantly lower weight loss during storage. Epibrassinolide declined fruit weight loss by retarding the respiration rate and physiological metabolisms during postharvest life of peach and jujube fruit [Zhu et al 2010, Ge et al 2016.…”
Section: Discussionmentioning
confidence: 96%
“…In agreement with our result, BR treated green bell pepper fruit maintained their green color during cold storage by delaying the decrease of chlorophyll content due to a low respiration rate ]. Wu and Yang [2016] demonstrated that exogenous BR was effective for the retention of green color in green asparagus. They also showed that BR treatment inhibited the degradation of chlorophyll, and a higher level of chlorophyll in BR-coated samples than control was observed after 24 days of storage at 4°C.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, according to the data obtained, the activity of PAL enzyme could be significantly inhibited by packaging and storage into PP C. Indeed, to maintain some qualitative characteristics of green asparagus, it could help the inhibition or regulation of this enzymatic activity [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…The measuring method of the chlorophyll content in the asparagus was utilized, with slight modification of Wu & Wang's method [28]. In brief, 2 g asparagus was ground in a mortar and extracted in 10 mL of 95% (v/v) ethanol and centrifuged at 6000 rpm for 15 min.…”
Section: Chlorophyllmentioning
confidence: 99%